Polynomial End Behavior Leave a Comment / By doina@highschoolmathtests.com / March 1, 2023 March 1, 2023 1. What is the end behavior of this polynomial function? \[f(x)=-x^{4}+4 x^{3}-2 x^{2}-7 x+3\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] 2. What is the end behavior of this polynomial function? \[f(x)=x^{3}-2 x^{2}-4\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] 3. What is the end behavior of this polynomial function? \[f(x)=-x^{5}+2 x^{3}-x+1\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] 4. What is the end behavior of this polynomial function? \[f(x)=x^{4}-2 x^{2}\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] 5. What is the end behavior of this polynomial function? \[f(x)=-x^{4}+3 x^{2}+1\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow-\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow-\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] \[\begin{array}{l} f(x) \rightarrow+\infty \text { as } x \rightarrow-\infty \\ f(x) \rightarrow+\infty \text { as } x \rightarrow+\infty \end{array}\] 1 out of 5 Time's upTime is Up!